2016
DOI: 10.1007/s40093-015-0111-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic amendments on sand dune fixation

Abstract: Background Poor physical and chemical properties of sand dune soil are the main constrains in afforestation of sand dune in desertified area. The aim of this study is to improve the physical and chemical properties of dune soil in Elrawakeeb Dry Land Station using organic wastes as a fertilizer source and amendments, for sustainable sand dune stabilization program. Salvadora persica L. seedlings were transplanted in a 2 m 9 2 m plots and treated with: sawdust (SW), chicken manure (CH), chicken manure with sawd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…That could be explained by the fact that cow manure is a source of organic carbon. Similar results were obtained by [22][23], who showed an increase in soil organic carbon with increased cow manure application.…”
Section: Soil Organic Carbon (% )supporting
confidence: 87%
“…That could be explained by the fact that cow manure is a source of organic carbon. Similar results were obtained by [22][23], who showed an increase in soil organic carbon with increased cow manure application.…”
Section: Soil Organic Carbon (% )supporting
confidence: 87%
“…Therefore, replacing chemical fertilizers with organic fertilizers or combine it with organic fertilizers is required to improve soil fertility. Numerous studies have reported that the application of organic fertilizers to soils of arid and semiarid regions enhances significantly soil fertility through improving soil properties compare to application of mineral fertilizers (Diacono and Montemurro 2010;Elhadi et al 2016;Elnesairy et al 2016;Hati et al 2006). Organic fertilizers such as animal manures have a considerable amount of nutrients in organic form and hence is not immediately available to the plant until decomposition by heterotrophic soil microorganisms occurs (Ladd and Jackson 1982).…”
Section: Introductionmentioning
confidence: 99%
“…El tiempo para alcanzar la estabilización fue prolongado, pudiendo atribuirse a la alta relación C/N de los residuos utilizados. Elhadi et al, 2016 observaron que, dependiendo del material original agregado al suelo y la cantidad del mismo, la dinámica del contenido de CO varía, aumentando inicialmente para después declinar hasta volverse estable. En nuestro trabajo, la estabilización del material y disminución del CO se observó entre los 9 y 12 meses desde la incorporación.…”
Section: Resultados Y Discusiónunclassified
“…La aplicación de enmiendas orgánicas afecta significativamente el nitrógeno mineral del suelo (NH 4 -N y NO 3 -N) después de 6 meses, en especial los tratamientos con estiércol de gallina (Elhadi et al, 2016), en contraste, los suelos con aserrín disminuyeron en la concentración de NO 3 del suelo a menos de 0.5 mg / kg por día (Clark et al, 2007).…”
Section: Resultados Y Discusiónunclassified